Coating residual stress effects on fatigue performance of 7050-T7451 aluminum alloy - Marin de Camargo, Jose Andre; Cornelis, Herman Jacobus; Odila Hilario Cioffi, Voorwald Maria; Pitanga Costa, Midori Yoshikawa (Elsevier B.V., 2007)
The tendency of the aircraft industry is to enhance customer value by improving performance and reducing environmental impact. In view of availability, aluminum alloys have a historically tendency to faster insertion due to their lower manufacturing and operated production infrastructure. In landing gear components, wear and corrosion control of many components is accomplished by surface treatments of chrome electroplating on steel or anodizing of aluminum. One of the most interesting environmentally safer and cleaner alternatives for the replacement of hard chrome plating or anodizing is tungsten carbide thermal spray coating, applied by the high velocity oxy fuel (HVOF) process. However, it was observed that residual stresses originating from these coatings reduce the fatigue strength of a component.An effective process as shot peening treatment, considered to improve the fatigue strength, pushes the crack sources beneath the surface in most of medium and high cycle cases, due to the compressive residual stress field induced. The objective of this research is to evaluate a tungsten carbide cobalt (WC-Co) coating applied by the high velocity oxy fuel (HVOF) process, used to replace anodizing. Anodic films were grown on 7050-T7451 aluminum alloy by sulfuric acid anodizing, chromic acid anodizing and hard anodizing. The influence on axial fatigue strength of anodic films grown on the aluminum alloy surface is to degrade the stress-life performance of the base material. Three groups of specimens were prepared and tested in axial fatigue to obtain S-N curves: base material, base material coated by HVOF and base material shot peened and coated.Experimental results revealed increase in the fatigue strength of Al 7050-T7451 alloy associated with the WC 17% Co coating. on the other hand, a reduction in fatigue life occurred in the shot peened and coated condition. Scanning electron microscopy technique and optical microscopy were used to observe crack origin sites, thickness and coating/substrate adhesion. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: fatigue; Al7050-T7451; tungsten carbide cobalt; shot peening; anodization